Investigation of electrical resistivity and magnetotransport properties of the La0.67Ca0.33Mn0.99Fe0.01O3 perovskite oxide - Dayal, Vijaylakshmi; Kumar, Punith V. (Solid state communications, 2013)
The electrical conductivity and magnetoresistance property of the bulk sample La0.67Ca0.33Mn0.99Fe0.01O3 has been reported, between the magnetic fields 0 and 5T and in temperature range 10–300K. Ferromagnetic metallic resistivity ρFM(T)=ρ0+ρ1Tn is observed well below the metal insulator (MI) transition temperature T<TMI. Above the metal insulator transition T>TMI the electrical conductivity is dominated by the Shklovskii–Efros variable-range hopping mechanism (SE-VRH), giving ρPM(T)=ρohexp[(T0/T)1/2]. Based on the scenario that the doped manganites consists of phase separated ferromagnetic metallic and paramagnetic insulating regions, a good fit of ρ(T) is well described by combining the contribution of ρFM(T) and ρPM(T) by the single expression between the temperature region 33 and 300K. Above TMI the ρ(T) also gives satisfactory fit and is well described using the small polaronic model (SPC) and Mott's VRH. At T≥TMI, a critical behavior of ρ(T) obeys the scaling law ρ−1(T)∼(1−(T/TMI))v. Investigations of magnetoresistance (MR) using magnetic field up to 5T shows two kinds of contribution: one is intrinsic MR and the other is extrinsic MR, which has been accounted fairly well by a phenomenological model based on spin polarized tunneling. ► The electrical and magnetic properties of La0.67Ca0.33Mn0.99Fe0.01O3 is studied. ► ρ(T) is analyzed by empirical relation for T<TMI and SPC, Mott and SE-VRH for T>TMI. ► The MR behavior with fields is explained in view of spin polarized tunneling.